C. Rajagopalachari - Murthi, R. K. (Publications Division, Ministry of Information and Broadcasting, Govt. of India, 2002)
Biography of Chakravarti Rajagopalachari, 1878-1972, Governor-General, 1948-1950, and statesman of India.